The Nexus Between International Trade, Exchange Rates, and Domestic Price Levels - Setiawan, Dion Ramadhan; Anggraeni, Kristin Dwi (Journal of Policy and Sustainable Development Studies, 2026)
Inflation is a critical monetary phenomenon that significantly influences a country’s economic conditions, including in Indonesia. This study aims to analyse the relationships between Exports, Imports, Exchange Rates, Interest Rates, and the Money Supply and the level of Inflation in Indonesia over one Decade. Data was obtained from Bank Indonesia, the Central Bureau of Statistics and the Ministry of Trade of the Republic of Indonesia. This study uses time series data from January 2015 to September 2024. Data analysis uses multiple linear regression using the Ordinary Least Squares (OLS) approach. The study's results indicate that the variables Export, Import, Interest Rate, and Money Supply have a significant effect on Inflation. Meanwhile, the Exchange Rate variable has no significant effect. However, through the F-test, it was found that simultaneously the variables of Export, Import, Exchange Rate, Interest Rate, and Money Supply have a significant effect on the Inflation rate in Indonesia.